From the Archive to the Field: A Report on Summer 2014 Asia Minor Travel Seminar: The Greek Orthodox Christians of Ottoman Cappadocia (July 20-August 11, 2014) - Papademetriou, Tom (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2015)
[ Δε διατίθεται περίληψη / no abstract available]